Alignment of the hindfoot in total knee arthroplasty: a systematic review of clinical and radiological outcomes. (1st January 2021) - Burssens, Arne; De Roos, Dries; Barg, Alexej; Welck, Matt J.; Krähenbühl, Nicola; Saltzman, Charles L.; Victor, Jan
Abstract : Aims: Patients with a deformity of the hindfoot present a particular challenge when performing total knee arthroplasty (TKA). The literature contains little information about the relationship between TKA and hindfoot alignment. This systematic review aimed to determine from both clinical and radiological studies whether TKA would alter a preoperative hindfoot deformity and whether the outcome of TKA is affected by the presence of a postoperative hindfoot deformity. Methods: A systematic literature search was performed in the databases PubMed, EMBASE, Cochrane Library, and Web of Science. Search terms consisted of "total knee arthroplasty/replacement" combined with "hindfoot/ankle alignment". Inclusion criteria were all English language studies analyzing the association between TKA and the alignment of the hindfoot, including the clinical or radiological outcomes. Exclusion criteria consisted of TKA performed with a concomitant extra-articular osteotomy and case reports or expert opinions. An assessment of quality was conducted using the modified Methodological Index for Non-Randomized Studies (MINORS). The review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines and registered in the PROSPERO database (CRD42019106980). Results: A total of 17 studies were found to be eligible for review. They included six prospective and ten retrospective studies, and one case-control study. The effects of TKA showed a clinical improvement in the hindfoot deformity in three studies, but did not if there was osteoarthritis (OA) of the ankle (one study) or a persistent deformity of the knee (one study). The radiological alignment of the hindfoot corrected in 11 studies, but did not in the presence of a rigid hindfoot varus deformity (in two studies). The effects of a hindfoot deformity on TKA included a clinical association with instability of the knee in one study, and a shift in the radiological weightbearing axis in two studies. The mean MINORS score was 9.4 out of 16 (7 to 12). Conclusion: TKA improves both the function and alignment of the hindfoot in patients with a preoperative deformity of the hindfoot. This may not apply if there is a persistent deformity of the knee, a rigid hindfoot varus deformity, or OA of the ankle. Moreover, a persistent deformity of the hindfoot may adversely affect the stability and longevity of a TKA. These findings should be interpreted with caution due to the moderate methodological quality of the studies which were included. Therefore, further prospective studies are needed in order to determine at which stage correction of a hindfoot deformity is required to optimize the outcome of a TKA. Cite this article: Bone Joint J 2021;103-B(1):87–97.